Octreotide-mediated tumor cell uptake and intracellular pH-responsive drug delivery of the self-assembly supramolecular nanocarrier. (May 2013) - Niu, Jiangxiu; Huang, Aiwen; Xiao, Yanyu; Su, Zhigui; Li, Hongying; Ping, Qineng; Bao, Xiao; Li, Sai; Chen, Yinan; Sun, Mingjie
Abstract In this study, DOX-loaded supramolecular nanocarrier (DLSC) was assembled by using two new amphiphilic polymers, octreotide-polyethylene glycol monostearate (OPMS) and N-octyl-N-succinyl O-carboxymethyl chitosan (OSCC). The characteristics of the DLSC were investigated. The results indicated that the significant pH-triggered release in vitro. The cellular uptake of DLSC was much higher than that of DOX-loaded OSCC micelles (DLOM) in the SMMC-7721 (somatostatin receptor (SSTR) over-expressed cell) cells, which suggested the SSTR-mediated properties. A considerable amount of drug entered the nucleus due to the pH-triggered deformation of the supramolecular structure and rapid release of drug in acidic endosomes of tumor cells. The killing efficacy was much higher than that of DLOM in the SMMC-7721. In S180 sarcoma-bearing KM mice, the biodistribution and therapeutic activity were studied. DLSC showed extended circulation time in plasma, decreasing drug concentrations in the heart and accumulating drug concentrations in the pancreas and tumor. In addition, minimized weight changes and cardiac toxicity, high suppression ratio of tumor growth and longer survival time were observed after intravenous injection of DLSC. The studies suggested that the supramolecular nanocarrier constructed of different designated polymers with multiple functions would be one of the most effective approaches for active targeting drug delivery.